Characterization of age hardening treatment of AA6061 Aluminium alloy through destructive and non-destructive testing techniques - Toozandehjani, Meysam (2014)
The aim of this research is to characterize the microstructural variation and mechanical properties of interest within the precipitation hardening of aluminum alloy of AA6061-T6 using conventional methods and non-destructive ultrasonic measurements. The study focuses on the using of ultrasonic non-destructive evaluation methods for the purpose of material characterization and consequently correlating the ultrasonic parameters; velocity and attenuation with the microstructure evolution and certain mechanical properties during the age hardening of 6061-T6 alloy. To achieve the proposed research objectives, aluminum plates of 6061-T6 aluminum alloy solutionized at 530 °C followed by quenching in iced water. Then, specimens were subjected to artificial aging heat treatment at 220 ºC for time periods of 30 min to 8 hours. The microstructure variation was analysed using Scanning Electron Microscopy (SEM) and optical microscopy to observe the important feature of microstructure such as precipitates before and after being aged. Specimens were then undergone to destructive test including Vickers hardness test (HV) and tensile test. Microhardness, yield strength (YS),ultimate tensile strength (UTS) and elongation of specimens were evaluated. Fracture surfaces of tensile samples were analyzed by SEM. The ultrasonic parameters; ultrasonic velocity and attenuation were measured. Longitudinal waves employed to calculate the velocity and the attenuation coefficient of waves. In addition, data analysis fuction was employed in order to indicate the accuracy and reliability of the results and percentages of error. A major part of the present work was dedicated to the effect of aging treatment parameter (aging time) on the microstructure and mechanical properties of 6061- T6 alloy. The results exhibited prominent microstructural changes and occurrence of different precipitation during aging as confirmed by SEM. The results indicated that a good combination of mechanical properties can be achieved by employing the heat treatment procedure. The optimum aging condition was enhanced after two hours of aging at 220 °C. It is believed that formation of precipitates contribute to variation in the mechanical behavior of the material. Further, ultrasonic measurement revealed a good correlation with microstructural features and mechanical properties measurements generated from destructive tests mentioned earlier. In the case of accuracy and reliability of results, data analysis showed a good consistency with a minimum error in the experimental results.